Isolation and Identification of Individual Palm Carotenes using Supercritical Fluid Chromatography - M.H, Ng; Y.M, Choo; A.N, Ma; C.H, Chuah; Ali Hashim, Mohd. (Malaysian Journal of Science, 2006)
A method for the isolation of individual carotenes in palm oil using supercritical fluid chromatography (SFC) is reported. While the isolation of individual carotenes in palm oil has been carried out in the past using high performance liquid chromatography (HPLC), SFC nevertheless offers more powerful and efficient separating properties as well as being a clean, hygienic and non-toxic method. In the past, the identification of individual carotenes was carried out based on the wavelength where they absorb maximum UV (Î»). With the new SFC method developed, it was found that the data obtained in the past for identification of individual carotenes dissolved in hexane solution can not be applied for their identifications in a supercritical fluid environment. Thus, the study on the behaviour of Î» of the individual carotenes in supercritical carbon dioxide has been carried out and reported. The data collected on the Î» of the individual carotenes in supercritical carbon dioxide environment will serve a useful purpose in their analyses and identification in the future.